흉부 디지털 영상의 병변 유무 판단을 위한 딥러닝 모델 - 이종근(Jong-Keun Lee); 김선진(Seon-Jin Kim); 곽내정(Nae-Joung Kwak); 김동우(Dong-Woo Kim); 안재형(Jae-Hyeong Ahn) (한국정보통신학회논문지, 2020)
There are dozens of different types of lesions that can be diagnosed through chest X-ray images, including Atelectasis, Cardiomegaly, Mass, Pneumothorax, and Effusion. Computed tomography(CT) test is generally necessary to determine the exact diagnosis and location and size of thoracic lesions, however computed tomography has disadvantages such as expensive cost and a lot of radiation exposure. Therefore, in this paper, we propose a deep learning algorithm for judging the presence or absence of lesions in chest X-ray images as the primary screening tool for the diagnosis of thoracic lesions. The proposed algorithm was designed by comparing various configuration methods to optimize the judgment of presence of lesions from chest X-ray. As a result, the evaluation rate of lesion presence of the proposed algorithm is about 1% better than the existing algorithm. 흉부 영상을 통해 진단 가능한 병변은 무기폐, 심비대, 덩어리, 기흉, 삼출 등 그 종류가 수십 가지에 이른다. 흉부 병변의 정확한 진단과 위치 및 크기를 판단하기 위해 일반적으로 전산화단층촬영(CT) 검사가 필요하지만, 전산화단층촬영은 검사 비용과 방사선 피폭 등의 단점이 있다. 따라서 본 논문에서는 흉부 병변 진단의 일차적 선별도구로서 방사선검사(X-ray) 영상에서 병변 유무 판단을 위한 딥러닝 알고리즘을 제안한다. 제안하는 알고리즘은 병변의 유무 판단에 최적화하기 위해 다양한 구성 방법들을 비교하여 설계하였다. 실험 결과, 기존 알고리즘보다 병변 유무 판단률이 약 1% 정도 향상되었다.